Recent Progress in the Development of New Antimalarial Drugs with Novel Targets - Belete TM (Dove Medical Press, 2020)
Tafere Mulaw Belete Department of Pharmacology, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Tafere Mulaw Belete Tel +251 918045943Email mutafere@yahoo.comAbstract: Malaria is a major global health problem that causes significant mortality and morbidity annually. The therapeutic options are scarce and massively challenged by the emergence of resistant parasite strains, which causes a major obstacle to malaria control. To prevent a potential public health emergency, there is an urgent need for new antimalarial drugs, with single-dose cures, broad therapeutic potential, and novel mechanism of action. Antimalarial drug development can follow several approaches ranging from modifications of existing agents to the design of novel agents that act against novel targets. Modern advancement in the biology of the parasite and the availability of the different genomic techniques provide a wide range of novel targets in the development of new therapy. Several promising targets for drug intervention have been revealed in recent years. Therefore, this review focuses on the progress made on the latest scientific and technological advances in the discovery and development of novel antimalarial agents. Among the most interesting antimalarial target proteins currently studied are proteases, protein kinases, Plasmodium sugar transporter inhibitor, aquaporin-3 inhibitor, choline transport inhibitor, dihydroorotate dehydrogenase inhibitor, isoprenoid biosynthesis inhibitor, farnesyltransferase inhibitor and enzymes are involved in lipid metabolism and DNA replication. This review summarizes the novel molecular targets and their inhibitors for antimalarial drug development approaches.Keywords: drug resistance, novel targets, antimalarial agents, mode of action, Plasmodium